EFL Students' Perceptions of English Pronunciation Difficulties - Hartatya Novika (Lembaga Pengembangan Kinerja Dosen, 2025)
Pronunciation is a crucial element of spoken English proficiency, yet it often receives insufficient emphasis in English as a Foreign Language (EFL) instruction, leading to persistent difficulties that affect learners’ intelligibility and confidence. This study investigates Indonesian EFL students’ perceptions of their English pronunciation challenges, aiming to identify the most problematic phonological features and understand learners’ interpretations of these difficulties. Employing a qualitative case study design, semi-structured interviews were conducted with six first-year students from the English Language Education Program at Universitas Islam Kalimantan (UNISKA) Banjarmasin. Participants were purposively selected based on their coursework and willingness to reflect on their pronunciation experiences. Findings reveal that segmental features such as the /θ/, /ð/, /v/, and vowel length contrasts, alongside suprasegmental aspects like word stress and intonation, pose significant challenges. These difficulties negatively impact learners’ speaking confidence and communicative engagement. The study underscores the importance of integrating learner perspectives into pronunciation pedagogy to enhance instructional effectiveness. Future research should explore intervention strategies and technology-assisted pronunciation learning tailored to diverse linguistic backgrounds.